Empirical investigation of underwater blast - Malan, Danie F (Department of Mechanical Engineering, 2014)
Background Most demolition practitioners seem to accept that an explosive charge is placed in direct contact with the target surface. Placing the charge in this way may be very convenient, but from an under water demolition point of view, this may not be the most effective placement. It should be noted that an underwater charge can be used in two distinctly different types of application against a target ' a large charge at a distance from the target (eg a torpedo) or a small charge in direct contact (eg demolition charge or limpet mine). In the first type of application a very large charge is detonated at a relatively large offset distance (typically 500kg at 10 meters or more). This type of application relies on extensive damage to and subsequent disruption of equipment on board a ship. The second type of application involves a small charge (typically 10 to 50kg) in direct contact with the target. The effect of this type of application is very localised and very severe, causing flooding and/or local structural failure. The work of this dissertation focuses on the second type of application which is a relatively small charge in contact or at very close offset distance (as opposed to a large charge at a large distance). It is often stated by experienced users in underwater explosions, that the damage caused by an underwater explosion is greater when the close proximity charge is physically slightly offset from the target surface. At the same time, none of these users could offer any specific rule or guideline that can be used to determine the optimum offset distance for any given charge or target. Most demolition users believe that a contact charge is the best way. In addition, they follow a rule of thumb: 'If in doubt, double the charge'. An important tendency of modern demolition work is to achieve better results with a smaller charge by improving the efficiency of the application. This implies either a better result with the same charge mass or the required effect with a smaller charge mass. If the demolition objective is well defined, the mass of explosive can be minimised. This would save cost and, in case of man-carried munition, save effort by the carrier. The principles, phenomena and effects of demolition in an air environment are very different from demolition under water. A principle difference is that a submerged detonation creates a pulsating gas bubble. Such a bubble is absent in an explosion in air. This thesis is focused on underwater detonations. It is well known that about half of the energy of an underwater detonation is transferred to the gas bubble (see Figure A), therefore it is fair to assume that the gas bubble associated with an underwater detonation should cause significant damage to a target (over and above the effect of the shock impulse). This 'significant damage' is a term that is usually used in a casual way and is hardly ever quantified.